AN ANALYSIS OF AFFIXATION IN SELOKO ADAT ” TUNJUK AJAR” (MORPHOLOGYCAL REVIEW) - Muhammad Rabik; Asridayanti Asridayanti; Dedi Efendi (Krinok:Jurnal Linguistik Budaya, 2022)
This research analyzes the affixation used in Seloko Adat “Tunjuk Ajar” in Jambi Province, Merangin Regency, Tabir District, to be precise in Tanjung Ilir village. The aims of the research are: (1) to identify the type of affixation in Seloko Adat that used in “Tunjuk Ajar” in Tanjung Ilir Village, Tabir District, Merangin Regency, Jambi Province; (2) to describe the function of affixation in Seloko Adat that used in “Tunjuk Ajar” in Tanjung Ilir Village, Tabir District, Merangin Regency, Jambi Province.The method used is a qualitative descriptive method based on the theory of Bogdan and Taylor in Moleong (2003:3). Then the researcher used the theory by Plag (2003:107) and Lieber (2009:39 and is also supported by Richard's theory (1985:184) for the type and function of affixation in Seloko Adat that used in “Tunjuk Ajar”. The researcher uses Non-Participant Observation Technique (SBLC) method to collect the data. Then the data were analyzed using the Referential method, and using formal and informal techniques to present the results of the research.The source of the data was taken from the Jambi Malay customary law Tabir version, by Baihaki, Lubuk Bumbun Village. This research was conducted in Tanjung Ilir Village, Tabir District, Merangin Regency, Jambi Province. The data collected were analyzed based on the type of affixation, namely prefix, suffix, confix, infix, circumfix, but in Seloko Adat “Tunjuk Ajar” there are only three types such as prefix, suffix, and confix. Seloko Adat “Tunjuk Ajar” were calculated by percentage of kinds which are the most dominant form of affixation. Percentage of affixation in Seloko Adat “Tunjuk Ajar” has totally 46 data, namely the prefix 39 data (84.7%), the suffix 5 data (10.8%) and the confix 2 data (4.3%). prefix is the most dominant affixation among other affixes that is 39 data (84 %) in the traditional seloko "Tunjuk Ajar".